Gambaran Karakteristik Ibu Hamil dalam Pemeriksaan Antenatal Care di Puskesmas Pasir Panjang Kota Kupang - Fransisca Camellia Bunga Wago; Engelina Nabuasa; Deviarbi S. Tira (Media Kesehatan Masyarakat, 2021)
Maternal mortality according to World Health Organization is death during pregnancy or within a period of 42 days after the end of pregnancy, due to all causes related to or aggravated by pregnancy or its handling, but not due to accident or injury. The causes of maternal death can be divided into two groups, namely direct obstetric death and indirect obstetric death. One of the efforts to reduce the Maternal Mortality Rate (MMR) is by providing standard Antenatal Care (ANC) services. This research aims to describe the characteristics of mothers in Antenatal Care examinations at the pubic health center of Pasir Panjang, Kupang City. This type of research used a descriptive design with a population of all K4 pregnant women register data at the pubic health center of Pasir Panjang in January-December 2019 as many as 403 pregnant women. Sampling using a total sampling technique of 403 pregnant women. The results showed that the characteristics of mothers according to age were in the 20-35 year old group (83.4%), parity in the nulliparous group (45.9%), residence in Pasir Panjang village (33.5%), history of maternal ANC visits according to the consecutive trimester of age Trimester I (98,1%), Trimester II (88,1%), and Trimester III (90.3%).